2013
DOI: 10.1371/journal.pone.0069295
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Activated Cl− Channels of the ClCa Family Express in the Cilia of a Subset of Rat Olfactory Sensory Neurons

Abstract: The Ca2+-activated Cl− channel is considered a key constituent of odor transduction. Odorant binding to a specific receptor in the cilia of olfactory sensory neurons (OSNs) triggers a cAMP cascade that mediates the opening of a cationic cyclic nucleotide-gated channel (CNG), allowing Ca2+ influx. Ca2+ ions activate Cl− channels, generating a significant Cl− efflux, with a large contribution to the receptor potential. The Anoctamin 2 channel (ANO2) is a major constituent of the Cl− conductance, but its knock-ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 34 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…3, A-C). The presence of IP 3 R3-positive nonsensory, microvillous epithelial cells in the apical compartment of the olfactory epithelium is documented elsewhere (Hegg et al 2010). This apical compartment also contains the apical dendrites and dendritic knobs of OSNs.…”
Section: Three Subtypes Of Vgscs Are Expressed In Osnsmentioning
confidence: 91%
See 1 more Smart Citation
“…3, A-C). The presence of IP 3 R3-positive nonsensory, microvillous epithelial cells in the apical compartment of the olfactory epithelium is documented elsewhere (Hegg et al 2010). This apical compartment also contains the apical dendrites and dendritic knobs of OSNs.…”
Section: Three Subtypes Of Vgscs Are Expressed In Osnsmentioning
confidence: 91%
“…In the second transgenic line (MMRRC STOCK Itpr3tm1.1Rmnc) a tau-GFP construct (tauGFP) placed under the control of the Itpr3 regulatory elements is expressed by a population of nonneuronal microvillous cells situated high in the olfactory epithelium but that do not extend an axon to the olfactory bulb and are not OSNs (Hegg et al 2010). The animals were housed on a 14-h light cycle with access to standard chow ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…However, the role played by TMEM16B/ANO2 in olfaction is controversial. Indeed, knockout mice for TMEM16B did not show any difference in olfactory sensitivity compared with wild-type mice [ 24 ] suggesting that this protein may be dispensable for normal olfaction, although another study [ 27 ] indicated that additional members of the CLCA family may also participate in the process of olfactory transduction together with TMEM16B, and substitute TMEM16B when it is absent.…”
Section: Introductionmentioning
confidence: 99%
“…A calcium-activated chloride channel (Clca2) (63) exhibited a higher FPKM value in the NKCC1-deficient transcriptome. This chloride channel is expressed in a subset of OSNs and may play a role in odorant transduction in cilia (64). Moreover, protocadherin 10 (Pcdh10), a gene with key roles in suppressing cell proliferation (65), displayed a higher FPKM value in NKCC1-deficient mice.…”
Section: Discussionmentioning
confidence: 99%